Towards the development of a standard test protocol : application of the MMLS3 for evaluating the performance of surfacing seals - Abrahams, Mohammad Shafee (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.